The Dietary Inflammatory Index and Hepatic Health in the Us Adult Population - Garcia-Hermoso, A (John Wiley and Sons Inc, 2022)
Background: There is limited evidence on the role of an anti-/pro-inflammatory diet in the prevention of non-alcoholic fatty liver disease (NAFLD). We aimed (i) to assess the anti-inflammatory diet profile and its association with transient elastography parameters, including liver stiffness measurement (LSM) and controlled attenuation parameter (CAP), and (ii) to analyse the relationship between the anti-inflammatory diet and surrogate markers of liver disease in a multiethnic US population. Methods: A cross-sectional study was conducted on a nationally representative population of 4189 US adults aged 20–80 years. A FibroScan® 502 V2 device (Echosens) was used to estimate the CAP and LSM. Liver markers, including the aspartate transaminase (AST) to alanine transaminase (ALT) ratio, fatty liver index (FLI) and fibrosis-4 score, were also calculated. The Dietary Inflammatory Index (DII) was calculated using a 24-h diet recall. Results: Lower DII scores (anti-inflammatory diet) were associated with a lower AST:ALT ratio (p < 0.001) and FLI (p < 0.036) after adjusting for covariates. Linear regression analysis revealed that gamma-glutamyl transferase levels (β = 1.702, 95% confidence interval [CI] = 0.325–3.080, p = 0.015), ALT levels (β = −0.616, 95% CI = −1.097 to −0.135, p = 0.012), AST:ALT ratio (β = 0.025, 95% CI = 0.014–0.036, p < 0.001) and FLI (β = 1.168, 95% CI = 0.224–2.112, p = 0.015) were significantly associated with the DII in the multivariable-adjusted model. Participants in the highest anti-inflammatory tertile had the lowest odds ratio (OR) for NAFLD assessed by FLI in both unadjusted (OR = 0.652, 95% CI = 0.539–0.788, p ≤ 0.001) and adjusted models (OR = 0.722, 95% CI = 0.537–0.972, p = 0.032). For the transient elastography parameters (LSM and CAP), no significant associations were identified. Conclusions: There was no relationship between the transient elastography parameters and the anti-inflammatory diet profile, although our study showed an association between higher pro-inflammatory properties of diet and poorer hepatic health assessed by surrogate markers of liver disease. Therefore, strategies to promote an anti-inflammatory diet should be considered to prevent NAFLD in adults. © 2021 The Authors. Journal of Human Nutrition and Dietetics published by John Wiley & Sons Ltd on behalf of British Dietetic Association.